Sleep assessment in adults with Down syndrome: correlation between functionality and polysomnographic findings - Callegari, Marilia Rezende; dos Santos, Kelly Brito; de Oliveira, Barbara Valente; Amorim, Ana Rita Avelino; Cymrot, Raquel; Blascovi-Assis, Silvana Maria (Arquivos de Neuro-Psiquiatria, 2023)
Background Sleep disorders have a negative impact on health, being associated with neurocognitive problems, cardiovascular diseases and obesity, influencing children's development and learning.Objective To assess the sleep pattern of people with Down syndrome (DS) and correlate changes with functionality and behavior.Methods A cross-sectional study was conducted to evaluate the sleep pattern in adults with DS > 18 years old. Twenty-two participants were assessed using the Pittsburgh Sleep Quality Index, the Functional Independence Measure and the Strengths and Difficulties Questionnaire, and the 11 who presented indications of disorders by the screening questionnaires were referred to polysomnography. Statistical tests were performed using a significance level of 5%, including sample normality tests and correlation tests (sleep and functionality).Results Impairment in sleep architecture was found due to an increase in the rate of awakenings in 100% of the participants, a decrease in the number of slow waves, and a high prevalence of sleep disordered breathing (SDB), with higher averages in the Apnea and Hypopnea Index (AHI) in the group. There was a negative correlation between sleep quality and global functionality (p = 0.011) and the motor (p = 0.074), cognitive (p = 0.010), and personal care (p = 0.072) dimensions in the group. Global and hyperactivity behavior changes were related to worse sleep quality (p = 0.072; p = 0.015, respectively).Conclusion There is an impairment in the sleep quality of adults with DS, with an increase in the rate of awakenings, a decrease in the number of slow waves, and a high prevalence of SDB affecting this population in the functional and behavioral aspects.
Keywords: Down Syndrome; Sleep; Sleep Wake Disorders; Polysomnography; Physical Functional Performance